Keberanjakan Hukum Waris Islam: Studi Perundangan Hukum Waris Negara Turki dan Somalia - Miftahul Huda (Justicia Islamica, 2007)
Keberanjakan Hukum Waris Islam: Studi Perundangan Hukum Waris Negara Turki dan Somalia Abstract This study aims to analyze the shift of Islamic inheritance law in the context of national legislation with a focus on the inheritance legal system in Turkey and Somalia. This study explores how the two countries implement and adapt Islamic inheritance principles in their respective legal systems, as well as the factors that influence these changes. The method used is library research with a descriptive-comparative approach. The research sources include Islamic law literature, national legislation, and related academic studies. The results showed that Turkey adopted a civil law-based inheritance legal system with significant secularization, while Somalia still maintained elements of Islamic inheritance law in its legislation. Historical, political, and social factors were the main determinants in the differences in the implementation of inheritance law in the two countries. This study provides insights into the dynamics of Islamic law adaptation in the context of a modern state.